Faktor Penghambat Pelaksanaan Evaluasi Program Bimbingan dan Konseling oleh Guru Bimbingan dan Konseling - Rahmi Dwi Febriani; Triyono Triyono (Universitas PGRI SUMATERA BARAT, 2018)
This research was conducted from the factors inhibiting the implementation of the guidance and counseling program evaluation by teachers and guidance counseling. The research objective was to describe factors inhibiting the implementation of the guidance and counseling program evaluation by teachers guidance and counseling. This research is a quantitative descriptive. The population the guidance and counseling teachers amounting 89 people. Also 30 teachers there were chosen by random sampling cluster. The instrument used in this study was a questionnaire. The data obtained were analyzed by using descriptive statistic. The results of this study revealed that: 1) A total of 31.1% of teacher’s guidance and counseling experiencing barriers to internal factor guidance and counseling program evaluation. 2) A total of 28.4% of teacher’s guidance and counseling experiencing barriers to external factors guidance and counseling program evaluation.